2004
DOI: 10.1103/physreva.70.032706
|View full text |Cite
|
Sign up to set email alerts
|

Calculations of electron-impact single-ionization cross sections of helium isoelectronic systems

Abstract: The electron-impact single-ionization cross sections on the helium isoelectronic targets He, Li + , B 3+ , C 4+ , N 5+ , O 5+ , Ne 8+ , Na 9+ , Fe 24+ , Ag 45+ , and U 90+ , are calculated using the recent simplified version of the binary-encounter dipole (siBED) model as applied by Huo [Phys. Rev. A 64, 042719 (2001)] to various molecular targets. The simple siBED model is good for the helium atom, but it is inadequate for ionic targets. Our proposed modifications: (i) ionic correction of the siBED model (QIB… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
11
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 50 publications
2
11
0
Order By: Relevance
“…RMPS calculations [8,21] have also been done for the electron impact excitation processes on Be 3+ ions. Detailed study of electron impact ionization cross sections have been reported for the Be isoelectronic ions using various theoretical approaches such as two potential distorted wave approximation [22], simplified improved binary-encounter dipole model (siBED) [23,24], QIBED (with the ionic correction) and RQIBED (with both the ionic and relativistic corrections) [25]. Electron impact cross sections for beryllium and beryllium hydrides have also been reported recently [26].…”
Section: Introductionmentioning
confidence: 99%
“…RMPS calculations [8,21] have also been done for the electron impact excitation processes on Be 3+ ions. Detailed study of electron impact ionization cross sections have been reported for the Be isoelectronic ions using various theoretical approaches such as two potential distorted wave approximation [22], simplified improved binary-encounter dipole model (siBED) [23,24], QIBED (with the ionic correction) and RQIBED (with both the ionic and relativistic corrections) [25]. Electron impact cross sections for beryllium and beryllium hydrides have also been reported recently [26].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, Kim et al extended the binary-encounter-dipole model to the relativistic energy region of the incident electron and calculated the K-shell ionization cross sections by electron impact [7,8]; this model was also applied most recently to calculate the L-shell x-ray production cross sections by electron impact [9]. Uddin et al employed the modified version of the improved binary-encounter-dipole model, into which the ionic and relativistic effects have been incorporated, to calculate the K-shell ionization cross sections by electron impact in a wide range of atomic number from Z = 6 to 50 and in the energy region up to about 10 MeV [10,11]. Colgan et al [3] and Segui et al [2] recently developed relativistic distorted-wave Born approximation theories (DWBA) to calculate K, L-shell ionization cross sections by electron/positron impact.…”
Section: Introductionmentioning
confidence: 99%
“…Crandall et al [5], Donets and Ovsyannikov [6], Rachafi et al [7], Duponchelle et al [8], and Marrs et al [9,10]; and the results from the parent HEMP model [2], the RQIBED model of Uddin et al [11] and available calculations from quantal methods. The latter includes the fit formula to the distorted wave Born approximation (DWBA) calculations of Younger [12], the analytic fit formula of Fontes et al [13] coined here as FRDWBA, emerging from the relativistic DWBA theory including the Breit interaction [14], and the relativistic DWBA theory with the inclusion of the Mller interaction [15] plus exchange (RDWBA) of Moores and Reed [16].…”
Section: Resultsmentioning
confidence: 99%